HUBUNGAN DUKUNGAN SOSIAL DENGAN RESILIENSI PADA ORANG TUA YANG MEMILIKI ANAK BERKEBUTUHAN KHUSUS - Ardea Magfira Syafni; Humairah Basmawati; Khairunnisa; Rukiana Novianti Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relationship between social support and resilience among parents of children with special needs. Parents of children with special needs often experience complex caregiving demands involving emotional, social, economic, and educational challenges. In such conditions, resilience becomes an essential psychological capacity that enables parents to adapt positively and maintain effective caregiving roles. Social support is considered an external protective factor that strengthens resilience through emotional assistance, practical help, information, and a sense of belonging. This study employed a quantitative correlational design involving 49 parents of children with special needs. Data were collected using Likert-type scales measuring social support and resilience. The data were analyzed using validity testing, reliability testing, classical assumption tests, simple linear regression, t-test, F-test, and coefficient of determination with SPSS version 29. The results indicated that all items were valid and reliable. The data were normally distributed, the relationship between variables was linear, and no heteroscedasticity was found. The regression analysis showed a coefficient of 0.732 with a significance value of < 0.001. The R value was 0.717, and the R Square value was 0.514, indicating that social support explained 51.4% of the variance in resilience. Therefore, social support has a positive and significant relationship with resilience among parents of children with special needs. Higher perceived social support is associated with higher parental resilience.